Oncofertility to Evidence‐Based Practice: Changes in Fertility Intention and Symptom Burden in Reproductive‐Age Women With Breast Cancer. Issue 5 (31st May 2019) - Huang, Sheng‐Miauh; Tseng, Ling‐Ming; Lai, Jerry Cheng‐Yen; Lien, Pei‐Ju; Chen, Ping‐Ho
Abstract: Background: Infertility is negatively related to the quality of life in reproductive‐age women with breast cancer. The nurses who care for these patients lack a comprehensive understanding of the changes in fertility intention that patients undergo from the time of cancer diagnosis, throughout treatment, and after treatment. A fertility intention assessment is the first step in discerning the patient's ideas toward future pregnancy. Aims: This study examined the changes in fertility intention and symptom burden in reproductive‐age women with breast cancer before, during, and after treatment. We also explored predictors of fertility intention among the women. Methods: The study was guided by the theory of planned behavior. A longitudinal and observational study was conducted with 151 women with breast cancer who were treated at a teaching hospital in Taipei. The participants were interviewed using a structured questionnaire before, during, and after chemotherapy from July 2016 to March 2018. Fertility intention was assessed using the Fertility Intention Scale. The M.D. Anderson Symptom Inventory‐Taiwanese version was used to measure the symptom burden. The generalized linear mixed model was used for multivariate analysis. Results: Patients had significantly lower scores for fertility intention after treatment than before treatment. The study patients had substantially worse symptom burden during treatment than before or after treatment. Symptom burden scores, especially for symptom interference, correlated significantly with fertility intention. A higher Fertility Intention Scale score was significantly associated with younger age. Linking Evidence to Action: Fertility intention decreased over time in women with breast cancer. Understanding fertility intention and controlling symptom burden throughout the course of treatment and beyond might help nurses provide better care for preserving fertility and maintaining fertility options for these women with breast cancer.